Resistance to ionic pt insertion in oxygen excess LaMnO3 perovskite lattices and its effect in water gas shift reaction - Rajesh, Thattarathody; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2014)
Pt doped and impregnated LaMnO3 perovskites are synthesized at different temperatures and Pt and Mn states are compared in an attempt to get insight into extent of lattice incorporation of Pt in perovskite. Various characterization studies indicate that oxygen excess system like LaMnO3 presents substantial resistance to B site doping with Pt. This behavior is different from other oxygen deficient perovskites like LaCoO3 and LaFeO3 in which lattice incorporation stabilizes the active species against sintering. Water gas shift reaction was used as a probe reaction to understand the effect of this difference in the activity. In case of LaMnO3, failure in lattice substitution leads to sintering and deactivation at high synthesis temperatures (>= 700 degrees C) in both impregnated and doped samples. In doped samples, however, a strong interaction of Pt species with a persistent amorphous phase prevents sintering at lower synthesis temperature thereby enhancing the activity when compared to impregnated sample. The study reveals a possible mechanism in which only Pt(0) species is active with perovskite playing a minimal role in this system due to the resistance to lattice incorporation. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Oxygen excess; Perovskites; Water gas shift reaction; XPS; XRD

Photocatalytic H-2 evolution from water-methanol mixtures on InGaO3(ZnO)(m) with an anisotropic layered structure modified with CuO and NiO cocatalysts - Narendranath, Soumya B.; Thekkeparambil, Saranya V.; George, Leena; Thundiyil, Shibin; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2016)
InGaO3(ZnO)(m) series of oxides is found to be active for photocatalytic H-2 evolution from water-methanol mixtures. The structure of this series is highly anisotropic with InO6 octahedral layers sandwiching Ga/ZnOn polyhedra. The structural anisotropy in which the conducting layer is spatially separated from the charge generation sites may help in suppressing charge recombination and consequently enhance catalytic activity. The band gaps of the series obtained from absorption spectra are above 3.6 eV and hence they are not active under visible light irradiation. H-2 evolution is considerably enhanced under UV light on employing NiO as cocatalyst due to facile electron transfer from InGaO3(ZnO)(m). to NiO. However, when CuO is used as cocatalyst, visible light activity could be brought out. Due to the very low band gap of CuO, it can act as a sensitizer absorbing in visible light. The band positions become conducive for H-2 evolution due to band alignments consequent to electron accumulation in CuO conduction band. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: InGaO3(ZnO)(m); photocatalytic water splitting; visible light; XPS; XRD